POETIC STUDIES IN THE LITERATURE OF MODERN UZBEK AND TURKISH WOMEN POETS - Arziqulova Sayohat Arziqulova, Arziqulova Sayohat Arziqulova (Scholar Express Journal, 2026)
This article examines the modern poetry of Uzbek and Turkish women poets, focusing on their formal innovations, thematic evolution, and artistic expression
Keywords: Women’s poetry, poetic genres, formal innovation, typology, lyrical imagery, “sarbast”, syllabic meter, rhyme, ignabarg, uchchanoq